Duodenal fatty acid sensor and transporter expression following acute fat exposure in healthy lean humans. Issue 2 (April 2017) - Cvijanovic, Nada; Isaacs, Nicole J.; Rayner, Christopher K.; Feinle-Bisset, Christine; Young, Richard L.; Little, Tanya J.
Summary: Background & aims: Free fatty acids (FFAs) and their derivatives are detected by G-protein coupled receptors (GPRs) on enteroendocrine cells, with specific transporters on enterocytes. It is unknown whether acute fat exposure affects FFA sensors/transporters, and whether this relates to hormone secretion and habitual fat intake. Methods: We studied 20 healthy participants (10M, 10F; BMI: 22 ± 1 kg/m 2 ; age: 28 ± 2 years), after an overnight fast, on 2 separate days. On the first day, duodenal biopsies were collected endoscopically before, and after, a 30-min intraduodenal (ID) infusion of 10% Intralipid ®, and relative transcript expression of FFA receptor 1 (FFAR1), FFA receptor 4 (FFAR4), GPR119 and the FFA transporter, cluster of differentiation-36 (CD36) was quantified from biopsies. On the second day, ID Intralipid ® was infused for 120-min, and plasma concentrations of cholecystokinin (CCK) and glucagon-like peptide-1 (GLP-1) evaluated. Habitual dietary intake was assessed using food frequency questionnaires (FFQs). Results: ID Intralipid ® increased expression of GPR119, but not FFAR1, FFAR4 and CD36, and stimulated CCK and GLP-1 secretion. Habitual polyunsaturated fatty acid (PUFA) consumption was negatively associated with basal GPR119 expression. Conclusions: GPR119 is an early transcriptional responder to duodenal lipid in lean humans, although this response appeared reduced in individuals with high PUFA intake. These observations may have implications for downstream regulation of gut hormone secretion and appetite. This study was registered as a clinical trial with the Australia and New Zealand Clinical Trial Registry (Trial number: ACTRN12612000376842).